Public Relation Strategy in Improving Brand Awareness of Bright Gas 5,5 kg at PT Pertamina (Persero) Mor III - Handy Martinus; Dinda Angelina (Humaniora, 2018)
The purpose of this research was to know the strategies used by public relations of PT PERTAMINA (Persero) MOR III to improve brand awareness of 5,5 Kg Bright Gas product, which was new. The research used a qualitative descriptive method by case studies, which had restricted clearly through the existing focus research. The technique of data collection also acquired through a semi-structured interview, observation, documentation, and research reference. This research would respond to the strategy of public relations of PT PERTAMINA (Persero) MOR III to improve brand awareness of 5,5 Kg Bright Gas product. Attainment from this research told that public relations of PT PERTAMINA (Persero) MOR III have done PENCILS strategy to improve brand awareness of 5,5 Kg Bright Gas product. It concludes that public relations have done all of PENCILS strategy, however, the implementation of the strategy is not yet fully maximum. There are still many things that need to be considered related to planning strategy which is more complete and ready.